2022
DOI: 10.1186/s13054-022-03945-x
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial hemorrhage in COVID-19 patients during extracorporeal membrane oxygenation for acute respiratory failure: a nationwide register study report

Abstract: Background In severe cases, SARS-CoV-2 infection leads to acute respiratory distress syndrome (ARDS), often treated by extracorporeal membrane oxygenation (ECMO). During ECMO therapy, anticoagulation is crucial to prevent device-associated thrombosis and device failure, however, it is associated with bleeding complications. In COVID-19, additional pathologies, such as endotheliitis, may further increase the risk of bleeding complications. To assess the frequency of bleeding events, we analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
2
6
0
1
Order By: Relevance
“…Second, our observation of higher than normal ICH rates in COVID-19 patients on ECMO stands not alone and has been reported by many groups around the globe, acknowledging both the critical combination of anticoagulation and a certain COVID-19–driven vascular susceptibility (4). Regarding choice of anticoagulation, UFH is used by the overwhelming majority of ECMO centers across the globe (5), whereas direct thrombin inhibitors are usually reserved for situations where UFH is contraindicated such as heparin-induced thrombocytopenia or plainly inefficient.…”
supporting
confidence: 53%
“…Second, our observation of higher than normal ICH rates in COVID-19 patients on ECMO stands not alone and has been reported by many groups around the globe, acknowledging both the critical combination of anticoagulation and a certain COVID-19–driven vascular susceptibility (4). Regarding choice of anticoagulation, UFH is used by the overwhelming majority of ECMO centers across the globe (5), whereas direct thrombin inhibitors are usually reserved for situations where UFH is contraindicated such as heparin-induced thrombocytopenia or plainly inefficient.…”
supporting
confidence: 53%
“…The bleeding complications of ECMO are usually related to anticoagulation and include gastrointestinal bleeding, craniocerebral hemorrhage, and airway hemorrhage. In COVID-19, in ammation, vascular endothelial injury, and coagulation disorders lead to the coexistence of thrombosis and bleeding risk; if anticoagulation is used in COVID-19 treatment, the bleeding risk may further increase [11,12]. Studies have shown that the incidence of major bleeding in patients with COVID-19 treated with ECMO is 30.9-42% [13,14], and airway bleeding accounts for 26% of the bleeding instances [14].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with IH were considerably younger than patients with AIS. von Stillfried et al reported the preferential use of ECMO therapy in younger patients with COVID-19 [ 22 ]. ECMO therapy is a risk factor for bleeding events and was also associated with the occurrence of IH in our study.…”
Section: Discussionmentioning
confidence: 99%